University Students’ Attitudes Towards Learning Grammar in a Multimedia-Enriched Environment - Prošić-Santovac, Danijela; Savić, Vera M.; Milutinović, Verica (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
A number of studies has shown that attitudes are one of the most significant and influential factors that determine success in learning a foreign language. The paper investigates university students’ attitudes towards learning grammar of the English language and towards the use of multimedia teaching tools in grammar instruction, and how these attitudes influence success in learning grammar. Our experimental study involved two groups of university students studying English as a foreign language, a control and an experimental group, in the course of a full academic year. The control group was taught using only the traditional tools, while grammar instruction for the experimental group was conducted in a multimedia-enriched environment, i.e. in addition to the traditional tools, the students were also exposed to educational video games and video clips in the form of film segments and music videos that were not part of a coursebook material, but were closely connected to the topic of the unit in the coursebook. It was hypothesised that positive attitudes towards learning grammar would affect achievements in learning grammar, and that the students exposed to the multimedia tools would be more inclined to view grammar in a positive light. The instruments applied in the study were an attitude questionnaire and a grammar test that yielded quantitative data for the statistical analysis. The results indicated that university students’ success in learning grammar was affected by their attitudes towards learning grammar, and that a multimedia-enriched environment contributed to the development of positive attitudes towards grammar. It can be concluded that positive attitudes towards multimedia-enriched environment in learning grammar resulted from the participants’ experience of purposeful application of multimedia in the language classroom, and that positive attitudes indirectly contributed to the participants’ success in the grammar test. These findings have significant implications for teaching grammar at a university level and can be used for improving the conditions for grammar teaching, enhancing motivation for learning grammar, and eventually for achieving better results in learning grammar in a foreign language classroom.